IMPLEMENTASI DIFUSI INOVASI PADA SISTEM SOSIAL TERKAIT DENGAN PENGGUNAAN E-TICKETING SEBAGAI PENGGANTI PEMBAYARAN TUNAI DAN SISTEM ANTRI (Survei Pada Mahasiswa Prodi Ilmu Komunikasi Universitas Bunda Mulia Sebagai Pengguna Moda Transportasi Commuter Line, - Girsang, Lasmery Rosentauly; Situmeang, Ilona Oisina (Universitas Bunda Mulia, 2014)
This research is titled “Hubungan Implementasi Difusi Inovasi Pada Sistem Sosial Terkait Dengan Penggunaan E-Ticketing Sebagai Pengganti Pembayaran Tunai dan Sistem Antri Terhadap Perilaku Mengadopsi (Survei Pada Mahasiswa Prodi Ilmu Komunikasi Universitas Bunda Mulia Sebagai Pengguna Moda Transportasi Commuter Line, Bekasi-Kota)” using mix method (quantitative and qualitative).Samples—taken from population 1045 from Communications Department’s students, University of Bunda Mulia, North Jakarta 2011-2014—are 91 persons through stratified random sampling. The hyphotesis are tested whereas there are relations among all (three) variables. Therefore, among diffusion of innovation, decision of innovation and behavior of adoption are related one another from validity (r hitung > r tabel) and reability (> 0.60). Also, strengthened by the results of in-depth interviews from ten key informants. As conclusion and suggestion, it is advised that government can improve facility for the user of commuter line while using e-ticketing as a form of an innovation. Keywords: Diffusion of Innovation, E-ticketing, Behavior of Innovation.